(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Organizations need to continually change in order to survive and to grow; this is especially true in the competitive markets andin market based economies. However, over emphasis on change can be a deterrent to organizational growth. It is thereforeessential to correctly identify areas and reasons for change. Critical decisions of identifying the areas, and order of change that would lead to a path of sustainability and growth for an organization require a decisive assessment process. At each phase of a decision making process, there are numerous nondeterministic choices and the certainty of success may be influenced by manyexternal factors. External factors affecting an organization include market forces such as, competition, user demand, and suppliers, in addition to political, legal, and environmental factors. These in turn influence internal efficiencies of its components: divisions, product lines, and Strategic Business Units- grouped together as Value Components (VC). In this paper, we present methodologies for organizations to recognize areas and rationale for change, and to identify options available for change. Our model for these methodologies is generic as it explores effective ways to leverage cooperative strategies for competitiveness and applies to all industries. We elaborate on issues and knowledgebase required for critical VC of a corporation, and on understanding the limits of efficiencies that can be achieved. A conceptual framework that emerges from the model provides systematic guidelines for critical decision making.